Perlindungan Hukum Tenaga Keperawatan dalam Menerima Pelimpahan Wewenang dari Kealpaan Tenaga Medis - Aziz, Abdul; Herisasono, Adi; Suwito, Suwito (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This paper is motivated by the implementation of an incident where nurses and midwives who received the delegation of authority could not read the writing from the Doctor which should be read on the Integrated Patient Progress Notes (CPPT) sheet but were read on the operation report sheet and the writing from the doctor was difficult to read. The purpose of this study is to analyze and find the negligence of Medical Personnel in granting delegation of authority to nursing staff and to analyze and find legal protection for Nursing personnel who carry out the delegation of authority from the negligence of medical personnel. Normative legal research, applying normative case mapping involving the results of legal actions, as well as analysis of government regulations. This study applies a qualitative approach. The results of this study have many implications for providing information on the following matters, namely; (1). Nursing personnel can be subject to criminal sanctions in carrying out the delegation of authority due to medical negligence (2) legal protection for nursing personnel who receive the delegation of authority from medical negligence. So, it is concluded that Nursing personnel can be subject to sanctions because the authority given to nursing personnel is not in accordance with their main duties and is not carried out in writing by the person giving the authority.